(untitled) (American Journal of Smart Technology and Solutions, 2024)
Soil tillage is one of the most critical processes in the agricultural production system, requiring the greatest energy and time of any operation. A cultivator with pulverizing attachment was designed and developed to reduce secondary tillage operations to a single pass to ensure timeliness in seedbed preparation. It consists of a pulverizing roller as an active unit and cultivator tynes as a passive unit. The implement has the following major components; a frame, cultivator tines, and a pulverizing roller consisting of central and peripheral shafts on which discs are arranged. The cultivator tynes were fitted on the main frame while the pulverizing roller was attached at the rear end of the frame with the help of bearings. The pulverizing blades were welded on discs in such a way as to crush the soil by impact force. In this way, the force exerted by the pulverizer on the clod is distributed uniformly in the shaft which is used to hold the pulverizing roller. The pulverizer was designed to break big clods formed during tillage operation and the implement was attached to the tractor by three point hitch. In operation, the cultivator tynes open the furrow, and the roller cuts and pulverizes the soil at optimum conditions for tillage. With a production cost of ETB 17,587.19, the implement is within the economic reach of an average smallholder farmer in Ethiopia.